Effects of polypropylene fibers and measurement methods on the yield stress of grouts for the consolidation of heritage masonry walls - Baltazar, Luis G. (2020)
FeDeR funds through the COMPeTe 2020 Programme under the project number POCI-01-0145-FeDeR-007688.